2017
DOI: 10.1021/acs.iecr.7b01612
|View full text |Cite
|
Sign up to set email alerts
|

Promotion Effect of Alkali Metal Hydroxides on Polymer-Stabilized Pd Nanoparticles for Selective Hydrogenation of C–C Triple Bonds in Alkynols

Abstract: Postimpregnation of Pd nanoparticles (NPs) stabilized within hyper-cross-linked polystyrene with sodium or potassium hydroxides of optimal concentration was found to significantly increase the catalytic activity for the partial hydrogenation of the C−C triple bond in 2-methyl-3-butyn-2-ol at ambient hydrogen pressure. The alkali metal hydroxide accelerates the transformation of the residual Pd(II) salt into Pd(0) NPs and diminishes the reaction induction period. In addition, the selectivity to the desired 2-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…It is noteworthy that all the initial samples were unreduced and contained Pd(II). As it was supposed in one of our previous publications [27] and also shown in the work of Hu K.-J. et al [28], formation of Pd NPs occurs effectively in situ in the presence of the substrate.…”
Section: Resultssupporting
confidence: 72%
“…It is noteworthy that all the initial samples were unreduced and contained Pd(II). As it was supposed in one of our previous publications [27] and also shown in the work of Hu K.-J. et al [28], formation of Pd NPs occurs effectively in situ in the presence of the substrate.…”
Section: Resultssupporting
confidence: 72%
“…The standard industrial synthesis route has involved the hydrogenation of alkynols over Pd catalysts . The existing literature on alkynol hydrogenation has focused on tertiary alkynols, notably 2-methyl-3-butyn-2-ol . The only reported transformation of secondary alkynols involved liquid-phase conversion of 3-butyn-2-ol using Pd/Al 2 O 3 in pressurized (oscillatory baffled vs stirred tank) reactors. , We have recently reported the formation of 2-butanol and 2-butanone as by-products in the continuous hydrogenation of 3-butyn-2-ol over a commercial Pd/Al 2 O 3 catalyst .…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that Pd NPs were mostly formed (during H 2 liquid-phase reduction of Pd/MN270-NaW at conditions of MBY hydrogenation) and probably are responsible for observed catalytic activity. Recently, we have found that the presence of alkali metals strongly influences the behavior (activity and selectivity) of hydrogenation catalysts synthesized while using chloridecontaining Pd salt [10]. Moreover, the sample treatments after impregnation with sodium carbonate accelerates precursor decomposition rendering Pd oxide and Pd NPs (see the results of XPS data).…”
Section: Suzuki Cross-coupling Results Of Catalytic Testing Of Pd/ Mmentioning
confidence: 99%
“…Pd-containing catalyst with calculated metal loading 1.5 wt.% was synthesized via conventional wet impregnation according to the procedure, which we described earlier elsewhere [9][10][11][12]. In a typical experiment, 1 g of pretreated (washed with distilled water and then with acetone), dried, and crushed (<70 μm) granules of HPS was impregnated with 2.7 mL of the Pd(CH 3 COO) 2 THF solution (concentration 0.058 mol/L).…”
Section: Catalyst Synthesis Hps-basedmentioning
confidence: 99%
See 1 more Smart Citation